The effects of destination image attributes and perceived risk on tourist travel intention - Mohd Asyraf Mohd Noor (2025)
This study draws new insight by examining the effects of destination image attributes and perceived risk on tourist travel intention and the mediating role of perceived risks between destination image attributes and travel intention of tourist to risky destination. This study used statistical package named SPSS 26.0 and SmartPLS 3 for data analysis.With destination image and perceived risk being empirically distinctive constructs, findings revealed that cognitive and affective images influence travel intention. Perceived risk were not affected by cognitive and affective image, although it directly influenced travel intention. Additionally, perceived risk did not significantly mediate the relationship between destination image attributes and travel intention. This study will extend the knowledge of destination image attributes, perceived risk and travel intention related to this study area in general and Malaysia in particular.